Mapping the emerging landscape of green waqf: A scoping review of Islamic philanthropy for the environment - Aditya Budi Santoso (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2026)
Background: Green waqf refers to the utilization of Islamic endowments for environmental conservation while simultaneously generating socio-economic benefits for communities. Beyond its practical dimension, green waqf carries significant academic value as it bridges Islamic finance, sustainable development, and public policy. This study aims to synthesize and analyze existing literature on green waqf to provide a comprehensive understanding of its conceptual development and practical implementation. Methods: Employing a scoping review approach, this research systematically maps the evolution of green waqf studies, identifies research gaps, and offers policy insights for optimizing its implementation. The analysis draws on secondary data from English-language scholarly publications published between 2015 and 2020, retrieved primarily from Google Scholar and Scopus databases, with an emphasis on open-access sources. Following the PRISMA-ScR guidelines to ensure transparency and accountability. Findings: The review identifies five thematic domains: (1) Conceptual and Theoretical Foundations of Green Waqf, (2) Descriptive-Analytical Studies (Practice Mapping), (3) Practical and Model Implementation, (4) Governance, Regulation, and Institutional Framework, and (5) Public Awareness, Education, and Socio-Religious Engagement. Findings reveal that research on green waqf remains dominated by conceptual studies, mainly focusing on foundational frameworks, strategic formulations, and proposed models, while empirical analyses remain scarce. Conclusion: Despite widespread acknowledgment of green waqf’s strategic potential to address socio-environmental challenges, its realization is hindered by institutional limitations, human resource capacity, regulatory constraints, and low public awareness. Strengthening the green waqf ecosystem therefore requires cross-sectoral policy harmonization among religious, forestry, energy, and financial institutions. Novelty/Originality of this article: The novelty of this study lies in its comprehensive mapping of green waqf research over the past decade, elucidating five thematic domains that clarify both theoretical and practical trajectories of green waqf development.